Clinical assessment of brain adaptation following multifocal intraocular lens implantation - Yutaro Nishi; Hiroyuki Nishi; Maiko Fukui; Miki Tatsumichi; Kayo Nishi; Okihiro Nishi (BMC Ophthalmology)
Abstract Purpose The purpose of this study was to clinically and quantitatively evaluate the speed of brain adaptation following multifocal intraocular lens (IOL) implantation. The speed of brain adaptation is considered to vary among individuals and influence postoperative visual recovery. Methods At our institution, a total of 24 cases underwent cataract surgery with the implantation of FineVision PodF (BVI/PhysIOL), PanOptix (Alcon), Intensity (Hanita Lenses), Tecnis Synergy (J&J), and Vivity (Alcon). The Mini-Mental State Examination (MMSE) test was performed postoperatively, at least one week after surgery. Patients whose corrected distance visual acuity (LogMAR) was better than 0 and who had no visual disturbance at 1 week postoperatively were classified as Group A (n = 14). Patients whose corrected distance visual acuity had not reached 0.1 and who still experienced visual disturbance at 1 month postoperatively were classified as Group B (n = 10). MMSE scores and test completion time for each group were retrospectively investigated as a pilot study. Results The mean age in Group A was 62 ± 10 years, and in Group B, 76 ± 5.6 years (p < 0.05). The MMSE test scores were 28.9 ± 1.7 points in Group A and 29.2 ± 0.69 points in Group B, showing no significant difference (p = 0.68). However, the MMSE test completion time was 256 ± 50 s in Group A and 346 ± 67 s in Group B, with a significant difference (p < 0.05). The percentage of patients completing the test within 5 min was 93% (13 out of 14) in Group A and 20% (2 out of 10) in Group B. Conclusion This study suggests that the speed of brain adaptation following multifocal IOL implantation may be reflected in MMSE test completion time. Future research is needed to further quantify brain adaptation speed using different IOL types, conditions, and refined test methods.